Interaction between Oxidative Stress and HDL Cholesterol Is Associated with Severity of Coronary Artery Calcification in Rheumatoid Arthritis - Rho, Young Hee (2010)
OBJECTIVES: We tested the hypothesis that oxidative stress is increased in patients with rheumatoid arthritis (RA) due to increased inflammation and contributes to the pathogenesis of atherosclerosis. METHODS: The independent association between urinary F(2)-isoprostane excretion, a measure of oxidative stress, and RA was tested using multiple linear regression models in 169 patients with RA and 92 control subjects frequency-matched for age, race and sex. The relationship between F(2)-isoprostane excretion and coronary calcium, a marker of atherosclerosis, was examined in multivariable proportional odds logistic regression models that also assessed the interactions between oxidative stress and LDL and HDL cholesterol. RESULTS: F(2)-isoprostane excretion (median [IQR]) was significantly higher in patients with RA (median 2.75 [interquartile range: 1.60-4.06] ng/mg creatinine (Cr)) than control subjects (1.86 [1.25-2.62] ng/mg Cr, adjusted p=0.006). In patients with RA, F(2)-isoprostanes were positively correlated with BMI (p<0.001) but not with disease activity or mediators of inflammation, such as DAS28 or serum TNF-α, IL-6 and CRP concentrations in adjusted multivariable models (all P>0.05). In patients with RA, F(2)-isoprostanes significantly modified the effect of HDL cholesterol on coronary calcification (p-value for interaction=0.02) after adjustment for age, sex and race. As F(2)-isoprostane levels increased, HDL lost its protective effect against coronary calcification. CONCLUSION: Oxidative stress measured as F(2)-isoprostane excretion was higher in patients with RA than control subjects. Among patients with RA, higher F(2)-isoprostane excretion and HDL cholesterol concentrations interacted significantly and were positively associated with the severity of coronary calcification.